Venona Project records - United States. Army. Signal Intelligence Service; Benson, Robert Louis; United States. National Security Agency/Central Security Service
Records relating to the Venona Project undertaken by the U.S. Army Signal Intelligence Service to examine encrypted Soviet diplomatic communications during World War II. Includes photocopies of translations of the communications in sixteen bound volumes titled, First Venona Release (11 July 1995), Second Venona Release (12 October 1995), Third Venona Release, 3 volumes, (March 1996), Fourth Venona Release, 4 volumes, (July 1996), and Fifth Venona Release, 7 volumes, (Oct. 1996). Also includes five guides written by Robert Louis Benson titled, Introductory History of Venona and Guide to the Translations, Venona Historical Monograph #2: The 1942-43 New York-Moscow KGB Messages, Venona Historical Monograph #3: The 1944-45 New York and Washington-Moscow KGB Messages, VENONA Historical Monograph #4: The KGB in San Francisco and Mexico City and The GRU in New York and Washington, and VENONA Historical Monograph #5: The KGB and GRU in Europe, South America, and Australia. Materials prepared by the U.S. National Security Agency/Central Security Service.
Venona Project records also available through the National Security Agency Central Security Service Web site.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: United States. -- Army. -- Signal Intelligence Service; World War, 1939-1945 -- Cryptography; World War, 1939-1945 -- Military intelligence -- United States; World War, 1939-1945 -- Soviet Union